Education on popular diseases to improve the quality of life for the people of Landungsari Village, Malang Regency - Arif Kusuma Firdaus; Ahmad Rizki Maulana; Fatita Rachma Laudira; Novitasari Agus Saputri; Ulya Zhafirah Wardah (University of Merdeka Malang, 2022)
Diabetes mellitus, heart disease, and joint disease are non-communicable diseases that are popular in the community. This disease is mostly suffered by the age group above 15 years which causes various complications, even death. The purpose of this program is to increase public knowledge and understanding of diseases, especially regarding how to prevent them, so that they can help improve the quality of public health. The method of community service activities is carried out by means of online and offline education and socialization which is carried out in three stages. The first stage is the preparation of activities, the second stage is the implementation of the activities, and the third stage is the evaluation and report generation. The results showed increased knowledge and understanding of the community about popular diseases which is marked by an increase in the posttest questionnaire score. Increase public knowledge and understanding of popular diseases that exist in the community, especially how to prevent disease in the hope of improving the quality of public health.